Caracterização Físico-Química e Desempenho de Motor Gerador Operando com Blendas de Biodiesel Óleo de Gergelim - Santos, Tatieli Knöner (2023)
Sesame (Sesamum indicum L.) oilseed needs to be studied in relation to the production of biodiesel and its application as an alternative to the soybean biodiesel used in Brazil. The aim of this study was to evaluate biodiesel blends (B0, B5, B10, B20, B40, B80, and B100) of sesame in terms of the performance and emissions of engines. Biodiesel was produced in the Automotive Technology Center (CTA) laboratory of the State University of West Paraná (UNIOESTE), Cascavel – Paraná using vegetable sesame oil. The fuels were tested in a 5-kVA generator engine at loads ranging from 1000 to 6000 W for each type of fuel. With the increase in load, there was a proportional reduction in O² emissions in all types of fuel. An increase in the sesame biodiesel blend caused a reduction in the specific fuel consumption (SFC), carbon monoxide (CO) emissions, and an increase in Nitrogen oxide (NOx) emissions. The emissions and performance of the sesame blends were similar to those of other alternative biodiesels. Therefore, sesame biodiesel, especially up to B20, is a viable alternative for the partial replacement of conventional diesel.